The Tensile Strength of Ice Containing Cracks. - Schulson, Erland M (1988)
Experiments have established that long, sharp cracks reduce the uniaxial tensile strength of equiaxed and randomly oriented aggregates of fresh-water ice strained at 0.001/s at -10 C, and that this reduction is in keeping with the dictates of linear elastic fracture mechanics. On the other hand, short cracks or long cracks that have been blunted by creep deformation have no effect on strength. In the latter cases, the tensile strength is controlled by the nucleation of new cracks and not by the propagation of pre-existing ones. Experiments have also established that the brittle compressive strength, sigma c, increases markedly with decreasing temperature but decreases with increasing strain rate. These effects are attributed to the controlling influence of shear crack sliding and, in turn, to the effects of temperature and sliding velocity on the coefficient of sliding friction, mu. The ratio of compressive to tensile strength appears to increase from around 8 at -10 C to around 15 at -50 C and is governed primarily by mu since, relative to the variation in sigma c, the tensile strength per se appears to vary little with temperature and strain rate. End constraint which imparts a radial compressive stress to ice raises the brittle compressive strength slightly and promotes crushing through shear faulting. End constraint which imparts a radial tensile stress lowers the strength slightly and promotes crushing through axial splitting.